Becoming who you are: An integrative review of self‐determination theory and personality systems interactions theory. Issue 1 (23rd April 2018) - Koole, Sander L.; Schlinkert, Caroline; Maldei, Tobias; Baumann, Nicola
Abstract: One of the enduring missions of personality science is to unravel what it takes to become a fully functioning person. In the present article, the authors address this matter from the perspectives of self‐determination theory (SDT) and personality systems interactions (PSI) theory. SDT (a) is rooted in humanistic psychology; (b) has emphasized a first‐person perspective on motivation and personality; (c) posits that the person, supported by the social environment, naturally moves toward growth through the satisfaction of basic psychological needs for autonomy, competence, and relatedness. PSI theory (a) is rooted in German volition psychology; (b) has emphasized a third‐person perspective on motivation and personality; and (c) posits that a fully functioning person can form and enact difficult intentions and integrate new experiences, and that such competencies are facilitated by affect regulation. The authors review empirical support for SDT and PSI theory, their convergences and divergences, and how the theories bear on recent empirical research on internalization, vitality, and achievement flow. The authors conclude that SDT and PSI theory offer complementary insights into developing a person's full potential.